Sex-Dependent Motor Deficit and Increased Anxiety-Like States in Mice Lacking Autism-Associated Gene Slit3 - Park, Su Mi; Plachez, Céline; Huang, Shiyong (Frontiers in Behavioral Neuroscience, 2018)
Altered neuronal connectivity has been implicated in the pathophysiology of Autism Spectrum Disorder (ASD). SLIT/ROBO signaling plays an important role in developmental processes of neuronal connectivity, including axon guidance, neuronal migration, and axonal and dendritic branching. Genetic evidence supports that Slit3, one of the genes encoding SLITs, is associated with ASD. Yet the causal link between Slit3 mutation and autism symptoms has not been examined. Here we assessed ASD-associated behaviors in Slit3 knockout (KO) mice. Our data showed that Slit3-KO mice exhibited reduced marble burying behaviors but normal social behaviors. In addition, Slit3-KO mice displayed hypolocomotion in the open field test and impaired motor coordination in the rotarod test. Anxiety-like behaviors were mainly observed in female KO mice assessed by three types of behavioral tests, namely, the open field test, elevated plus maze test, and light/dark box test. No differences were observed between KO and wildtype mice in recognition memory in the novel object recognition test or depression-like behavior in the tail suspension test. Taken together, loss of Slit3 may result in disrupted neural circuits related to motor function and increased anxiety-like states, which are co-occurring symptoms in ASD.